Reproductive compatibility and chromosome pairing in the Drosophila buzzatii complex - Madi-Ravazzi, L. [UNESP]; De Campos Bicudo, H. E.M. [UNESP]; Manzato, J. A. [UNESP] (My University, 1997)
Fertility (percentage of fertile crosses) and the degree of synapsis in salivary gland chromosomes in isofemale lines of Drosophila buzzatii, D. serido, D. koepferae and D. seriema were analysed. D. buzzatii was completely sterile in intercrosses with strains from the other species except for D. koepferae. The other species intercrossed to a greater or lesser degree, but also differed between crossing directions. Homologous pairing in salivary gland preparations of strains and hybrids conformed with the data on fertility. The lowest degree of synapsis was present in hybrids between D. koepferae and D. buzzatii, D. seriema and D. koepferae and D. koepferae and D. serido. These species also exhibited the lowest degree of reproductive compatibility. Hybrids between D. seriema and D. serido showed an intermediate degree of synapsis (pairing absent in the proximal and distal chromosome ends), as well as fertility greater than that found in the other interspecific crosses. Results of the fertility of crosses involving strains of a single species, compared with data in the literature, indicated that intraspecific divergence occurred in D. serido and D. koepferae.
Keywords: Chromosome pairing; Drosophila species; Fertility